Historia del pádel = History of padel - Bernardino Javier Sánchez-Alcaraz Martínez (Universidad Politécnica de Madrid, 2013)
El presente trabajo resume la historia del deporte del pádel. Existen dos versiones sobre el origen del pádel. La primera versión relaciona los antecedentes del pádel con los de otros deportes de raqueta como el tenis o el bádminton, siendo su origen común el jeu de la paume francés. Posteriormente, surgen variantes en Estados Unidos como el Paddle Tennis y el Platform Tennis, siendo versiones reducidas del tenis, pero con elementos muy comunes al pádel actual. La segunda versión, aprobada por la Federación Internacional de Pádel, afirma que este deporte nació en México, en 1969, a través del empresario Enrique Corcuera.   Abstract This research summarizes the history of paddle sport. There are two versions about the origin of paddle. The first version relates the history of paddle with other racket sports like tennis or badminton, and its common origin of the Jeu de Paume French. Later, in in the United States, appear two sports called Paddle Tennis and Platform Tennis, which are reduced versions of tennis sport, but these have lot of common characteristics with paddle. The second version, approved by the International Padel Federation, said the sport was born in Mexico in 1969, through the businessman Enrique Corcuera.